2016
DOI: 10.3390/ijms17071148
|View full text |Cite
|
Sign up to set email alerts
|

Potential Metabolic Biomarkers to Identify Interstitial Lung Abnormalities

Abstract: Determining sensitive biomarkers in the peripheral blood to identify interstitial lung abnormalities (ILAs) is essential for the simple early diagnosis of ILAs. This study aimed to determine serum metabolic biomarkers of ILAs and the corresponding pathogenesis. Three groups of subjects undergoing health screening, including healthy subjects, subjects with ILAs, and subjects who were healthy initially and with ILAs one year later (Healthy→ILAs), were recruited for this study. The metabolic profiles of all of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…LPC levels were elevated in serum samples from IPF patients as determined by ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry, and it was suggested that LPC could serve as a biomarker for IPF [249]. However, metabolomics analysis of peripheral blood samples from abnormal interstitial lung patients revealed downregulation of 1-acyl LPC but upregulation of PC, PA, and PE suggesting potential activation of lipid metabolizing enzymes during the development of interstitial lung abnormalities [250]. However, LPA, the major lysolipid linked to development of IPF, was not identified in the analysis.…”
Section: Lysophospholipids and Lysophospholipids Metabolizing Enzymesmentioning
confidence: 99%
“…LPC levels were elevated in serum samples from IPF patients as determined by ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry, and it was suggested that LPC could serve as a biomarker for IPF [249]. However, metabolomics analysis of peripheral blood samples from abnormal interstitial lung patients revealed downregulation of 1-acyl LPC but upregulation of PC, PA, and PE suggesting potential activation of lipid metabolizing enzymes during the development of interstitial lung abnormalities [250]. However, LPA, the major lysolipid linked to development of IPF, was not identified in the analysis.…”
Section: Lysophospholipids and Lysophospholipids Metabolizing Enzymesmentioning
confidence: 99%
“…It is the biomarker discoveries and the corresponding biological insights that enable metabolomics to change our understanding of the development of many chronic diseases. Up to now, metabolomics has found applications in many chronic metabolic disorders, such as diabetes, lung disease, neurodegenerative disease, cancer, hypertension, and cardiovascular diseases [3,4,5]. In recent years, metabolomics have gained popularity in the orthopedic field, including osteonecrosis, osteoarthritis, ankylosing spondylitis, bone tumors and osteoporosis [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the large scale sample analysis has no signi cant effect on the reliability of the data. 20…”
Section: Testing With the Gc-ms Methodsmentioning
confidence: 99%
“…\The linear retention indices of all components were determined by homologous n-alkanes (C 10 -C 40 ).These components were identi ed by comparing with the mass spectra of NIST05 and NIST05S. 20…”
Section: Gc-ms Analysismentioning
confidence: 99%